What is the quality of smoking cessation advice in guidelines of tobacco-related diseases? - Bogdanovica, Ilze; Agrawal, Sanjay; Gregory, Benjamin; Britton, John; Leonardi-Bee, Jo (Royal College of Physicians, 2015)
Smoking is a major risk factor for a range of diseases, and quitting smoking provides considerable benefits to health. It therefore follows that clinical guidelines on disease management, particularly for diseases caused by smoking, should include smoking cessation. The aim of this study was to determine the extent to which this is the case. We conducted a systematic review investigating clinical guidelines and recommendations issued by UK national or European transnational medical speciality associations and societies issued between 2000 and 2012 on a range of diseases caused by smoking. We then investigated whether selected guidelines contained reference to smoking cessation and smoking cessation advice. Although the extent to which smoking and smoking cessation was mentioned in the guidelines varied between diseases, only 60% of guidelines identified recognised that smoking is a risk factor for the development of the disease and 40% recommended smoking cessation. Only 19% of guidelines provided detailed information on how to deliver smoking cessation support. Smoking cessation is not comprehensively addressed in current UK and transnational European clinical practice guidelines and recommendations.